Cell-derived biomimetic nanocarriers for targeted cancer therapy: cell membranes and extracellular vesicles. (1st January 2021) - Li, Aixue; Zhao, Yunan; Li, Yixiu; Jiang, Liangdi; Gu, Yongwei; Liu, Jiyong
Abstract: Nanotechnology provides synthetic carriers for cancer drug delivery that protect cargos from degradation, control drug release and increase local accumulation at tumors. However, these non-natural vehicles display poor tumor targeting and potential toxicity and are eliminated by the immune system. Recently, biomimetic nanocarriers have been widely developed based on the concept of 'mimicking nature.' Among them, cell-derived biomimetic vehicles have become the focus of bionics research because of their multiple natural functions, such as low immunogenicity, long circulation time and targeting ability. Cell membrane-coated carriers and extracellular vesicles are two widely used cell-based biomimetic materials. Here, this review summarizes the latest progress in the application of these two biomimetic carriers in targeted cancer therapy. Their properties and performance are compared, and their future challenges and development prospects are discussed.